2014
DOI: 10.1084/jem.20140455
|View full text |Cite
|
Sign up to set email alerts
|

CCDC88B is a novel regulator of maturation and effector functions of T cells during pathological inflammation

Abstract: Kennedy et al. identify a mutation in coiled-coil domain containing protein 88b (Ccdc88b) that confers protection against lethal neuroinflammation during experimental cerebral malaria. CCDC88B is expressed in immune cells and regulates T cell maturation and effector functions. In humans, the CCDC88B gene maps to a locus associated with susceptibility to several inflammatory and autoimmune disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 66 publications
3
84
0
Order By: Relevance
“…Among the down-regulated genes, the only non-mitochondrial gene was CCDC88B, coding for coiled-coil domain containing protein 88b, that is expressed in lymphocytes and myeloid cells and may have a role in regulation of T-cell function during inflammation [64]. Interestingly, this gene showed an unusual behaviour in cells treated with different dilutions (Fig 5): its expression decreased in samples from cells treated with low dilutions of Arnica m .…”
Section: Discussionmentioning
confidence: 99%
“…Among the down-regulated genes, the only non-mitochondrial gene was CCDC88B, coding for coiled-coil domain containing protein 88b, that is expressed in lymphocytes and myeloid cells and may have a role in regulation of T-cell function during inflammation [64]. Interestingly, this gene showed an unusual behaviour in cells treated with different dilutions (Fig 5): its expression decreased in samples from cells treated with low dilutions of Arnica m .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our hypothesis we found that CD4-Cre Mysm1 fl/fl mice show increased survival. 46 In this study, we have identified a novel role for chromatin-interacting deubiquitinase MYSM1 in CD8 + T-cell development and function. No major differences in the IFN-c or TNF-a production by CD4 + or CD8 + T cells from the CD4-Cre Mysm1 fl/fl ECM mice was detected, prompting us to conclude that the improved survival of CD4-Cre Mysm1 fl/fl mice is probably dependent on the reduction of CD8 + T-cell numbers.…”
Section: Discussionmentioning
confidence: 87%
“…While revising our manuscript, HkRP3 (CCDC88B) was identified as a gene responsible for pathological inflammation via a genome-wide screen of ENU ( N -ethyl- N -nitrosourea)-mutagenized mice (46). Loss of HkRP3 was found to induce resistance in an experimental cerebral malaria (ECM) model, which normally leads to severe inflammatory responses and lethality.…”
Section: Discussionmentioning
confidence: 99%